Aplicações do princípio de Cavalieri ao cálculo de volumes e áreas - Lula, Kariton Pereira (2013)
In elementary mathematics teaching, it often occurs that some subjects are presented without proper justi cation or without a coherent logical construction that makes sense of those subjects and ideas in a wider context. The calculation of areas and volumes is an example of a subject in which these shortcomings are usually present. In this work, we present a model for the gradual development of the ideas involved in the calculation of volumes, in a way that is, at once, well justi ed and approachable by the average student at this stage. In order to achieve that, we make extensive use of the Cavalieri Principle, which allows not only an adequate justi cation of the expressions for the volume of cylinders, cones or spheres, but also the calculation of volumes of other shapes, such as parts of the sphere, ellipsoids and paraboloids. We conclude with an interesting application of the Cavalieri Principle to calculate the area of a parabolic segment and then give a demonstration of Archimedes' theorem.